Detection of adulteration in pure honey utilizing Ag-graphene oxide coated fiber optic SPR probes. (1st December 2020) - Vikas,; Yadav, Mahesh Kumar; Kumar, Pradip; Verma, R.K.
Highlights: SPR based fiber optic sensor for adulteration detection in pure honey is presented. Probes have been fabricated by utilizing silver and Ag-graphene oxide (GO) thin films. GO modified probe enhances sensitivity to 24% and 37% for glucose and fructose adulterated honey. Repeatability, Limit of Detection and Limit of Quantification has also been assessed. Easy, rapid, label free technique for the detection of glucose/fructose in pure honey. Abstract: Fiber optic surface plasmon resonance (SPR) sensor utilizing silver (Ag) and Ag-graphene oxide (GO) is designed and developed for the detection of adulteration of glucose and fructose in pure honey. The concentration range of the two adulterants in pure honey is varied from 4% to 20% with a step change of 4%. The experiments were performed with two different fiber optic probes viz. Probe 1 and Probe 2. Probe 1 is fabricated by coating 50 nm Ag film on unclad optical fiber portion and Probe 2 is fabricated by modifying Ag film with GO for sensitivity improvement. The study confirms that using GO modified fiber optic probe, the sensitivity is enhanced to 24% and 37% for glucose and fructose adulterated honey samples respectively. The technique presented in this study is easy, rapid, label free and shows high prospective for the detection of adulterants in pure honey.